If I Were You: Perceptual Illusion of Body Swapping - Petkova, Valeria I.; Ehrsson, H. Henrik (PloS one, 2008)
The concept of an individual swapping his or her body with that of another person has captured the imagination of writers and artists for decades. Although this topic has not been the subject of investigation in science, it exemplifies the fundamental question of why we have an ongoing experience of being located inside our bodies. Here we report a perceptual illusion of body-swapping that addresses directly this issue. Manipulation of the visual perspective, in combination with the receipt of correlated multisensory information from the body was sufficient to trigger the illusion that another person's body or an artificial body was one's own. This effect was so strong that people could experience being in another person's body when facing their own body and shaking hands with it. Our results are of fundamental importance because they identify the perceptual processes that produce the feeling of ownership of one's body.